Spatial influence of attractions on tourism development. Issue 5 (19th October 2016) - Truchet, Stéphanie; Piguet, Virginie; Aubert, Francis; Callois, Jean-Marc
ABSTRACT: Destination planning raises questions relative to spatial organization within the destination and to the spatial extent of the gains generated by attractions. Thus, it is important to increase understanding and knowledge of the mechanisms by which attractions generate tourism development. The aim of this study is to analyze how tourist attractions influence tourism development within destination and what the spatial extent of this influence is. It is argued that both the appeal of tourist attractions and their spatial characteristics are determining factors. Thus, distinguishing local, spread, and diffuse attractions is essential and specific indicators were created to that purpose. Using count data models, an econometric analysis was conducted in order to test the effect of attractions on the number of hotel rooms in 2015 on the one hand, and on the number of employees in the tourism sector in 2014 on the other, in French municipalities. The study brings several original results. First, as in the case of green areas, some attractions may trigger the emergence of tourism development but may also have a depressive effect on the level of tourism development when they exceed a certain threshold. Second, the influence of sport and leisure facilities is more limited in space than for ski slopes, beaches and tourist sites, which confirms that the appeal of attractions determine the spatial extent of tourism development. Third, beyond a distance threshold, some attractions can generate negative spatial spillovers and have a depressive effect on tourism development.